DEVELOPMENT OF E-COMIC LEARNING MEDIA FOR REDUCTION AND OXIDATION MATERIAL BASED ON FLIP PDF PROFESSIONAL ON THE DISCOVERY LEARNING (Universitas Negeri Surabaya, 2022)
This research and development aims to produce a valid, practical, and effective e-comic reduction and oxidation reaction based Flip PDF Professional. The development of this e-comic refers to the ADDIE development model which includes the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. The subjects in this study were 2 media experts and material experts, 1 people of chemistry teacher, and 30 students of class X MIPA 2 SMA Negeri 14 Makassar. The instruments used for validity are validation sheets by media experts and material experts, practicality, namely observation sheets on the implementation of e-comic, teacher and student response questionnaires, and learning outcomes tests. The results of this study are: (1) the validity of the digital comic from the media expert is 3.72 and the material expert is 3.75 which is in the very valid category with a consistency test between validators are 100% which is in very high criteria, (2) the average percentage of e-comic practicality is 97%, where the percentage of practicality based on the questionnaire responses of teachers and students to digital comic are 100% and 90,55% in the very practical category, 3) e-comic meet the effective criteria (â‰¥85%) based on the achievement of class completeness with percentage 86.67%. Based on these data, it is concluded that the e-comic reduction and oxidation reaction based Flip PDF Professional developed with the ADDIE model is valid, practical, and effective for use in learning